Two-stage pH-sensitive doxorubicin hydrochloride loaded core–shell nanoparticles with dual drug-loading strategies for the potential anti-tumor treatment. Issue 106 (1st November 2016) - Yu, Xiaoyue; Zhang, Bo; Wang, Tianqi; Zhang, Jing; Mu, Shengjun; Liu, Chunxi; Zhang, Na
Abstract : Two-stage pH-sensitive DOX·HCl loaded core–shell nanoparticles (CPOD) with dual drug-loading strategies showed pretty in vivo anti-tumor efficacy. Abstract : A novel two-stage pH-sensitive doxorubicin hydrochloride (DOX·HCl) delivery system, programmed to respond to tumor extracellular circumstrances (about pH 6.5) and intercellular endo/lysosome (pH 5.0), was designed with dual drug-loading strategies. Hydrazone linked cationic conjugates poly(ethyleneimine)-C6-succinimidyl 6-hydrazinonicotinate acetone hydrazone-DOX·HCl (PEI-C6-SANH-DOX·HCl, PEI-C-DOX) was synthesized, then condensed the DOX·HCl loaded 21-base (CGA)7 oligodeoxynucleotides (CGA-ODNs/DOX·HCl, OD) to get the dual methods DOX·HCl loaded nanoparticles PEI-C-DOX/OD (POD) as inner core. Subsequently, O -carboxymethyl-chitosan (CMCS) was coated on POD to construct the core–shell nanoparticles CMCS/POD (CPOD). The average size and zeta potential of CPOD were (165.0 ± 3.3) nm and −(15.6 ± 0.82) mV, respectively. In vitro evaluation showed that CMCS could dissociate from POD at tumor extracellular pH values, and the cellular uptake of CPOD was much higher than that at pH 7.4 ( p < 0.005 in B16 cells, p < 0.01 in HepG2 cells). Besides, in vitro release study revealed that the drug release amount from CPOD at endo/lysosome pH was significantly more than that at pH 7.4 ( p < 0.005), which was further indicated by nuclear localization test. In vivo NIRF imaging illustrated the accumulation in tumor of CPOD for 24 h. Furthermore, in vivo anti-tumor test indicated that CPOD exhibited more superior anti-tumor efficacy even than double dosage DOX·HCl solution. No visible tissue lesions of main organs in CPOD group were observed, indicating preliminary in vivo safety of CPOD. These results suggest that the two-stage pH-sensitive CPOD would be a promising delivery platform for improving anti-tumor efficacy of DOX·HCl with a fair degree of safety.